Meiotic synapsis of homeologous chromosomes and mismatch repair protein detection in the parthenogenetic rock lizard Darevskia unisexualis. Issue 2 (12th January 2021) - Spangenberg, Victor; Arakelyan, Marine; Galoyan, Eduard; Martirosyan, Irena; Bogomazova, Alexandra; Martynova, Elena; de Bello Cioffi, Marcelo; Liehr, Thomas; Al‐Rikabi, Ahmed; Osipov, Fedor; Petrosyan, Varos; Kolomiets, Oxana
Abstract: Parthenogenetic species of Caucasian rock lizards of the genus Darevksia are important evidence for reticulate evolution and speciation by hybridization in vertebrates. Female‐only lineages formed through interspecific hybridization have been discovered in many groups. Nevertheless, critical mechanisms of oogenesis and specifics of meiosis that provide long‐term stability of parthenogenetic species are still unknown. Here we report cytogenetic characteristics of somatic karyotypes and meiotic prophase I nuclei in the diploid parthenogenetic species Darevskia unisexualis from the new population "Keti" in Armenia which contains an odd number of chromosomes 2n = 37, instead of the usual 2n = 38. We revealed 36 acrocentric chromosomes and a single metacentric autosomal chromosome, resulting from Robertsonian translocation. Comparative genomic hybridization revealed that chromosome fusion occurred between two chromosomes inherited from the maternal species, similar to another parthenogenetic species D. rostombekowi . To trace the chromosome behaviour in meiosis, we performed an immunocytochemical study of primary oocytes' spread nuclei and studied chromosome synapsis during meiotic prophase I in D. unisexualis based on analysis of synaptonemal complexes (SCs). We found meiotic SC‐trivalent composed of one metacentric and two acrocentric chromosomes. We confirmed that the SC was assembled between homeologous chromosomes inherited from two parental species. Immunostaining of the pachytene and diplotene nuclei revealed a mismatch repair protein MLH1 loaded to all autosomal SC bivalents. Possible mechanisms of meiotic recombination between homeologous chromosomes are discussed.